Electrochemical Quartz Crystal Microbalance Study on Electrodeposition of Pt on Au-QCM - Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2013)
Platinum was electrodeposited on an Au-QCM in 40 mM H2PtCl6 solution using an electrochemical quartz crystal microbalance. At 0.2 V vs. SHE, a 4-electron reduction of Pt-ion took place. On the other hand, at 0.6 V a mixture of 2-electron and 4-electron reduction took place.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9328Journal of Nepal Chemical Society Vol. 30, 2012 Page: 1-4 Uploaded date: 12/16/2013